Effect of (Ni-Ag) co-doping on crystal structure and magnetic Property of SnO2. (29th November 2019) - Srivastava, S K; Brahma, R; Datta, S; Guha, Shampa; Aakansha,; Baro, S S; Narzary, B; Basumatary, D R; Kar, Manoranjan; Ravi, S
Abstract: In this work, a series of (Ni-Ag) co-doped SnO2 compounds i.e. Sn1-x-y Nix Agy O2 (x = 0–0.12 and y = 0–0.12) compounds have been prepared by the solid-state reaction route. The x-ray diffraction patterns (XRD) indicate that these compounds crystallize to rutile phase with tetragonal structure. Temperature variation of magnetization (M-T) of these compounds indicates that the co-doping of Ni and Ag in place of Sn in SnO2 gives rise the increase in magnetization. One of the striking features observed from the M-T measurement is the relatively large Curie temperature ( θ C ) in the order of 721.2 K and 675.7 K for Sn0.94 Ag0.06 O2 and Sn0.94 Ni0.06 O2 compounds. The θ C is found to decrease systematically upon Ni-Ag co-doping. The M-H curves at the room temperature indicate that the saturation magnetization, area under the hysteresis loop and the coercive field increases with the increase in (Ni-Ag) co-doping upto x = y = 0.06 (i.e. 6%). However, for further co-doping, these parameters were found to decrease.